Pengaruh Mekanisme Bonus dan Intangible Assets terhadap Transfer Pricing dengan Tax Avoidance sebagai Variabel Moderasi - Putri Anggraeni, Selvia; Nuryati, Tutty; Rossa, Elia; Puspaningtyas Faeni, Dewi; Manrejo, Sumarno (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
The purpose of this research is to analyze theories explaining the influence of bonus mechanisms and intangible assets on transfer pricing, with tax avoidance as a moderating variable. This study employs a quantitative approach through a literature review method. The research presents theoretical foundations, other explanatory variables, and findings from previous studies. The study is grounded in agency theory and signaling theory. Supportive variables influencing transfer pricing consist of bonus mechanisms and intangible assets, moderated by tax avoidance. The results indicate different relationships between bonus mechanisms and intangible assets concerning transfer pricing, as well as the relationship between tax avoidance in moderating bonus mechanisms and intangible assets concerning transfer pricing. This study aims to provide an overview to explain the occurring phenomenon.